Islam Awal dalam Cermin Narasi Kristen dan Yahudi - Gun Gun Gunawan (Jurnal Penelitian Ilmu Ushuluddin, 2026)
The study of early Islam faces historiographical challenges due to the limited availability of internal sources, making Christian and Jewish testimonies from the seventh to ninth centuries important primary references for reconstructing contemporary responses to the emergence of Islam. This article analyzes the narrative constructions of these two traditions through Byzantine, Syriac, and Latin chronicles, as well as Rabbinic and Jewish apocalyptic texts. The findings show that Christian sources are generally polemical, portraying Islam as a heresy or a political threat, while Jewish sources tend to present more ambivalent and pragmatic responses due to changes in their social status under early Islamic rule. The comparative analysis reveals that theological bias, socio-political position, and the context of political transition were the main factors shaping these representations. Although heavily imbued with ideological rhetoric, the factual data contained in these sources still make a significant contribution to the reconstruction of the history of Islam during its formative period. This study underscores the importance of utilizing non-Muslim sources as a critical and multidisciplinary complement in the historiographical study of early Islam.